Gender and Sexuality in Russian History: New Directions - Fraser, Erica (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
Gender history overall – not just for Russia – is at a crossroads right now. This article suggests that historians of Russian gender and sexuality need to pursue new methodologies, reframe older questions, and engage more with gender history in other geographical fields if we are to move forward. The present moment, with Russian president Vladimir Putin choosing to highlight gender and sexual identity in Russia through his “homosexual propaganda” law, is crucial for gender history, and Russianists are poised to provide leadership to the rest of the gender history field because of it. However, we must first overcome long-established obstacles such as following, rather than leading, in the kinds of questions we ask, and we must actively engage in dialogue with other fields on gender issues.